The lipid composition of Euphausla superba Dana in relation to the nutritional value of Phaeocystis pouchetii (Hariot) Lagerheim - Patti Virtue; Nichols, P; Nicol, S; Andrew McMinn; Sikes, E (1993)
The fatty acid profiles ofEuphausiusuperba, the Antarctic prymnesiophyte, Phaeocystispouchetii, and a temperate diatom, Phaeodactylum tricornutum were analysed and compared. The lipid content, lipid class, fatty acid and sterol composition ofE. superba fed on each cultured phytoplankton and amixed diet ofboth species, were determined. No significant difference was found between total lipid levels of E. superba reared on each of these different diets. Phaeocystispouchetii, although deficient in a number of the essential fatty acids, is apparently an adequate food source for E. superba. The proportion of polyenoic fatty acids varied within lipid classes although there was no significant difference between levels of the long chain polyunsaturate 20:5(n-3) in the total lipid of E. superba fed on these diets. This acid was found to be less than 1% of the total lipid in Phaeocystispouchetii compared to 37% in Phaeodactyhm tricornutum. This suggests that krill may possess the ability to convert exogenousshorter chainfatty acids to 20:5(n-3) and 22:6(n-3). Significantdifferencesweredetectedin theisomeric ratio of 16:1(n-7~)/16:0b etween krill fed the diatom compared to the prymnesiophyte diet. Significant differences were also detected in several shorter chain fatty acids and between fatty acids within their lipid classes. Such differences may have the potential to be used as biochemical signatures to provide information on food sources and possible feeding grounds of E. superba. Phaeocystispouchetii in a very late stationary phase, although not used in this feeding study, was found to contain 11 % of 22:6(n-3) for which there are few substantive sources in natural algal populations.